Unscheduled school closings and student performance - Dave E. Marcotte; Steven W. Hemelt (Institute for the Study of Labor (IZA), 2007)
Do students perform better on statewide assessments in years in which they have more school days to prepare? We explore this question using data on math and reading assessments taken by students in the 3rd, 5th and 8th grades since 1994 in Maryland. Our identification strategy is rooted in the fact that tests are administered on the same day(s) statewide in late winter or early spring, and any unscheduled closings due to snow reduce instruction time, and are not made up until after the exams are over. We estimate that in academic years with an average number of unscheduled closures (5), the number of 3rd graders performing satisfactorily on state reading and math assessments within a school is nearly 3 percent lower than in years with no school closings. The impacts of closure are smaller for students in 5th and 8th grade. Combining our estimates with actual patterns of unscheduled closings in the last 3 years, we find that more than half of schools failing to make adequate yearly progress (AYP) in 3rd grade math or reading, required under No Child Left Behind, would have met AYP if schools had been open on all scheduled days.
Keywords: 330; Bildungsniveau; Allgemeinbildende Schule; Betriebszeit; Maryland